Herbicidal activities of some allelochemicals and their synergistic behaviors toward amaranthus tricolor L. - Chotsaeng, Nawasit; Laosinwattana, Chamroon; Charoenying, Patchanee (My University, 2017)
Seven allelochemicals, namely R-(+)-limonene (A), vanillin (B), xanthoxyline (C), vanillic acid (D), linoleic acid (E), methyl linoleate (F), and (±)-odorine (G), were investigated for their herbicidal activities on Chinese amaranth (Amaranthus tricolor L.). At 400 μM, xanthoxyline (C) showed the greatest inhibitory activity on seed germination and seedling growth of the tested plant. Both vanillic acid (D) and (±)-odorine (G) inhibited shoot growth, however, apart from xanthoxyline (C), only vanillic acid (D) could inhibit root growth. Interestingly, R-(+)-limonene (A) lightly promoted root length. Other substances had no allelopathic effect on seed germination and seedling growth of the tested plant. To better understand and optimize the inhibitory effects of these natural herbicides, 21 samples of binary mixtures of these seven compounds were tested at 400 μM using 0.25% (v/v) Tween(r) 80 as a control treatment. The results showed that binary mixtures of R-(+)-limonene:xanthoxyline (A:C), vanillin:xanthoxyline (B:C), and xanthoxyline:linoleic acid (C:E) exhibited strong allelopathic activities on germination and seedling growth of the tested plant, and the level of inhibition was close to the effect of xanthoxyline (C) at 400 μM and was better than the effect of xanthoxyline (C) at 200 μM. The inhibition was hypothesized to be from a synergistic interaction of each pair of alleochemicals. Mole ratios of each pair of allelochemicals ((A:C), (B:C), and (C:E)) were then evaluated, and the best ratios of the binary mixtures A:C, B:C and C:E were found to be 2:8, 2:8, and 4:6 respectively. These binary mixtures significantly inhibited germination and shoot and root growth of Chinese amaranth at low concentrations. The results reported here highlight a synergistic behavior of some allelochemicals which could be applied in the development of potential herbicides.
Keywords: Allelopathy; Binary mixture; Chinese amaranth; Herbicidal; Linoleic acid; R-(+)-limonene; Synergistic; Vanillin; Xanthoxyline